2018
DOI: 10.5603/kp.a2017.0215
|View full text |Cite
|
Sign up to set email alerts
|

Favourable hypotensive effect after standardised tomato extract treatment in hypertensive subjects at high cardiovascular risk: a randomised controlled trial

Abstract: The results of this study show that the addition of STE to standard antihypertensive therapy improves BP control in hypertensive patients with high CV risk. This effect, together with the anti-aggregatory effect, may indicate the pleiotropic effect of tomato extract. This fact justifies further research into functional foods and gives new insights into STE as a food supplement that could have new therapeutic and prophylactic uses for the treatment of hypertensive patients with high CV risk and especially with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…However, in our previous study, we have not found any reduction in blood pressure following a 4-week treatment with ASA compared with standardized tomato extract (213 mg/ day). Both drugs were administered in the morning, and the treatment group included patients of high and very high cardiovascular risk [40]. Similar results were published by Avazini et al who did not observe a decrease in SBP and DBP in patients treated for hypertension with a low-dose ASA administered in the morning [19].…”
Section: Discussionsupporting
confidence: 58%
“…However, in our previous study, we have not found any reduction in blood pressure following a 4-week treatment with ASA compared with standardized tomato extract (213 mg/ day). Both drugs were administered in the morning, and the treatment group included patients of high and very high cardiovascular risk [40]. Similar results were published by Avazini et al who did not observe a decrease in SBP and DBP in patients treated for hypertension with a low-dose ASA administered in the morning [19].…”
Section: Discussionsupporting
confidence: 58%
“…Recently, an antiplatelet effect of tomato extract, mostly attributed to the presence of phenolic compounds, has been well documented in in vitro experimental studies. Its partial benefits in the primary prevention of CVD have been reported for obese subjects [11,12]. A growing interest has also been expressed in the use of mushrooms as functional foods [13,14], and, in recent decades, certain mushroom species have been experimentally found to exert antiplatelet effects through different pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Typical antiplatelet drugs have an irreversible mechanism of action (44,45). Similarly, ZAAX standardized tomato extract (Sequia) has also been found to possess antiaggregatory properties in high-risk hypertension patients: a study on a group of 82 patients aged 28-74 y who may be at high risk of cardiovascular disease found a dose of 213 mg orally in the morning to be effective at preventing aggregation (47), whereas Krasinska et al (48) note a positive correlation between blood platelet activation and P2Y12 receptor activity, particularly in obese patients. Some studies indicated that the bioactive component of tomatoes is lycopene, known to have antioxidant, antihypertensive, and hypolipidemic effects in vitro and in vivo (70,71).…”
Section: Tomato (Solanum Lycopersicum L)mentioning
confidence: 99%
“…Some studies indicated that the bioactive component of tomatoes is lycopene, known to have antioxidant, antihypertensive, and hypolipidemic effects in vitro and in vivo (70,71). In addition, although Thies et al (72) reported that lycopene may also have an effect on blood platelet activation, none of the studies of Fruitflow or ZAAX tomato extract described the concentration of lycopene in the preparations (44,45,47,48,46).…”
Section: Tomato (Solanum Lycopersicum L)mentioning
confidence: 99%